2010
DOI: 10.1097/01.pra.0000369969.87779.1c
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Parameters and Appetite Regulators in Patients with Anorexia Nervosa

Abstract: Anorexia nervosa (AN) has serious negative effects on multiple organs and systems of the human body. As patients often do not make their eating disorder the subject of discussion, the physician is forced to rely on the physical examination and laboratory parameters as diagnostic hints. Obvious signs of AN are a body mass index (BMI) below 17.5 kg/m, dry and scaly skin, lanugo, edema, acrocyanosis, petechias, dental problems, and low blood pressure. However, because the often complex laboratory alterations can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 66 publications
(60 reference statements)
0
17
0
2
Order By: Relevance
“…Literature data showed that ghrelin could partially be involved in the suppression of spontaneous secretion of LH in humans [22-24]. In pathological condition, such as anorexia nervosa where high serum ghrelin level and infertility are detected, a relation between these two features of the disorder could also be hypothesized [89-93]. Nevertheless, whether such a relationship exists indeed in humans, requires further elaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data showed that ghrelin could partially be involved in the suppression of spontaneous secretion of LH in humans [22-24]. In pathological condition, such as anorexia nervosa where high serum ghrelin level and infertility are detected, a relation between these two features of the disorder could also be hypothesized [89-93]. Nevertheless, whether such a relationship exists indeed in humans, requires further elaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Women who are acutely ill with anorexia nervosa have abnormally low gonadotropin, estrogen and progestin levels and usually amenorrhea, and women with bulimia nervosa frequently report menstrual dysfunction (30,332,334,483,566). In addition, testosterone levels are decreased in symptomatic women with anorexia nervosa and increased in symptomatic women with bulimia nervosa (30,504,709).…”
Section: Physiological Sex Differences In Disordered Human Eatingmentioning
confidence: 99%
“…In any case, the main pathways involved in eating behavior could be roughly summarized in central neurotransmission, especially serotonin, dopamine and, to lesser extent, noradrenaline, whose involvement in ED has been extensively studied; reward-related pathways, particularly the cannabinoid endogenous system (it has been suggested that AN patients have a dysregulation of this Obesity-associated genes in the etiopathogenesis of eating disorders Perspective system and that restriction and exercise become a way to compensate for diminished response to reward [39]) and central regulation of food intake, including ghrelin, an appetite-stimulating hormone that functions as a neuropeptide in the CNS and whose levels may be altered in women with AN [40]. In addition, a variety of other genes that do not strictly fit in this classification have been tested in genetic association studies with ED patients, albeit with generally inconsistent results [41][42][43][44][45][46][47][48][49].…”
Section: Candidate Genes In Biological Pathways Involved In Eating DImentioning
confidence: 99%